Emancipación familiar en Espa\~na: Análisis del comportamiento de los jóvenes en 1990, 2000 y 2010 - María Consuelo Colom Andrés; María Cruz Molés Machí (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– Over the past decades there have been structural changes in the developed societies, both demographic and economic changes. In this paper we aim to study which has been the influence of these changes on the path towards adulthood of youth. We analyzed the emancipation of young at three points in time, and we provide predictions for such decision by gender, academic attainment and labor occupation. Our results indicate that the behavior of young people towards family independence varies between men and women. We have found that men are more sensitive to economic changes and women accuse more the changes in the education system. With predictions, we observe that the pattern of behavior of the emancipation process has not varied in the last decade of the last century; however there are some changes in the first decade of the 21st century.
Keywords: J13; D12; C35; 330; family emancipation; academic level; labor activity; logit model